Design of radiation shielding for the 4-MeV RF linac using the Monte Carlo simulation - P. Jaikaew (2020)
© Published under licence by IOP Publishing Ltd. A radio-frequency (RF) linear accelerator (linac) and related system for irradiation of electron beam on natural rubber is under the commissioning at the PBP-CMU Electron Linac Laboratory, Chiang Mai University. The maximum kinetic energy of electron beam that can be achieved from the accelerator is about 4 MeV. The bremsstrahlung radiation in the X-ray regime is produced when electrons interact with materials in the beam path. The radiation with the dose exceeding the regulation limit can be harmful for the personnel in the laboratory and public area. This research concentrates on design of radiation shielding to prevent the leakage of radiation from the accelerator area. Calculation of the photon's energy deposition per volume due to the interactions of electron beam with materials in the irradiation system and surrounding area including the collision and bremsstrahlung processes was performed by using a Monte Carlo simulation software GEANT4. Shielding walls of the 4-MeV linac and its irradiation system consists of iron plates with the thickness of 2 cm for the side walls and 3 cm for the top wall. Results of the radiation calculation suggested that the photon's energy deposition per volume outside the accelerator hall reduces by more than 99.5% after the shielding walls were added.